Evaluation of the cognitive technical levels of the students of Diyala University - Iraq - Mahmoud, Yousry Abdel Wahab (Arab Journal for Sciences and Research Publishing, 2017)
The Paper aims at studying the problem of arts levels Cognitive. The study is limited to students in the University of Diyala in the academic Year 2014-2015. The survey study is adopted. In order to measure the aim, the tool has setting that is comprising (15) questions. Then, the reliability of the tool is founded as the ration of experts, The researcher found out a group of conclusions, most significant among them are:  -Students in the University of Diyala clearly suffer from arts which is arts levels Cognitive verified according to the study results. In the light of the study results, the researcher recommends the following: The necessity of reconsidering the syllabus of arts education in schools for it was set twenty years ago during which various developments took place in the field in Arabic and western countries , a fact that is urging us to follow their steps.-Enrolling current teachers in development and practical training courses relying on the syllabus attempting to improve their performance. We suggested making study, a comparative study arts levels Cognitive concerning among Iraqi Universities, students.